Harnessing the anticancer potential of Piper nigrum: a synergistic approach to chemotherapy enhancement and reduced side effects - Hesti Lina Wiraswati; Ilma Fauziah Ma’ruf; Nur Akmalia Hidayati; Julia Ramadhanti; Daniela Calina; Javad Sharifi-Rad (Discover Oncology)
Abstract Cancer therapy continues to face critical challenges, including drug resistance, recurrence, and severe side effects, which often compromise patient outcomes and quality of life. Exploring novel, cost-effective approaches, this review highlights the potential of Piper nigrum (black pepper) extract (PNE) as a complementary anticancer agent. Piper nigrum, a widely available spice with a rich history in traditional medicine, contains bioactive compounds such as piperine, which have demonstrated significant anticancer activities including cell cycle arrest, apoptosis induction, and inhibition of tumor growth and metastasis. The review evaluates the recent findings from in vitro, in vivo, and clinical studies, emphasizing PNE's capacity to enhance the efficacy of conventional chemotherapeutic agents while mitigating their side effects. Key mechanisms underlying these effects include oxidative stress modulation, suppression of pro-metastatic factors, and synergistic interactions with established drugs like doxorubicin and paclitaxel. These interactions suggest that PNE could play a pivotal role in overcoming chemoresistance and improving therapeutic outcomes. Furthermore, this review highlights the potential benefits of PNE in resource-limited settings, where the cost of cancer treatments often restricts access. However, challenges such as compositional variability, limited bioavailability, and the need for standardization and clinical validation need to be addressed to advance the integration of PNE into basic oncology. By providing a comprehensive analysis of the anticancer mechanisms of PNE and its potential as a cost-effective adjuvant therapy, this review provides new insight into the exploitation of Piper nigrum to improve cancer treatment efficacy while reducing side effects. Future research directions are discussed to address current limitations and facilitate clinical translation.